2019
DOI: 10.1007/s12034-019-1792-6
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of short sisal fibre polyester composites

Abstract: Natural fibres have the potential to replace synthetic fibres for making polymer composites because of their good engineering properties. Sisal fibres obtained from the leaves of the sisal plant exhibit high strength among various other natural fibres, but have not been yet fully explored. Nevertheless, the impact of sisal fibre in polymer composites depends on sisal fibre extraction process, characteristic of fibre, fibre binder ratios, synthesizing technique, etc. In the present study, a detailed experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…In particular, natural fibers reinforced with plastic composites have high mechanical properties, and have great potential in the application of packaging materials [1]. Previous works have confirmed that blending plastic with appropriate sisal, bagasse, bamboo flour (BF), flax, wood powder, or other cellulose fibers could significantly reinforce the mechanical properties of the plastic composite, especially the bending modulus and impact strength [2][3][4][5][6][7]. The physical properties, such as length, diameter, growth cycle, and cost, of the most-used natural fibers are listed in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, natural fibers reinforced with plastic composites have high mechanical properties, and have great potential in the application of packaging materials [1]. Previous works have confirmed that blending plastic with appropriate sisal, bagasse, bamboo flour (BF), flax, wood powder, or other cellulose fibers could significantly reinforce the mechanical properties of the plastic composite, especially the bending modulus and impact strength [2][3][4][5][6][7]. The physical properties, such as length, diameter, growth cycle, and cost, of the most-used natural fibers are listed in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Non-conventional or technical category involves textile applications which are based on the functional requirements. Sisal fibers are utilized as a reinforcing agent in making composites for varieties of technical applications including agro textiles, automotive, aerospace, upholstery, shades, sports, construction and geotextiles (Umair and Khan, 2020;Uppal et al, 2019;Richaud et al, 2017;Desai and Kant, 2016;Qin, 2016;Prabakar and Sridhar, 2002).…”
Section: Application Of Sisal Fibers In Textilesmentioning
confidence: 99%
“…al., (2023), doi: 10.52339/tjet.v42i2.916 depletion of the petrochemical resources and associated environmental footprint encourages the need for natural fibers (Salit et al, 2015b). Furthermore, synthetic fibers have negative environmental effects since they are nonbiodegradable thus attract needs for further research in natural fibers to replace the synthetic ones (Uppal et al, 2019;Balakrishnan et al, 2016). Sisal is among the most researched leaf fibers in the efforts to replace synthetic fibers (de Klerk et al, 2020;Naveen et al, 2018;Senthilkumar et al, 2018;Kumre et al, 2017;Sahu and Gupta, 2017a;Ibrahim et al, 2016).…”
Section: Sisal Fibers Vs Synthetic Fibersmentioning
confidence: 99%
See 1 more Smart Citation
“…Uppal et al [18] observed that composites containing short shredded sisal fibres have high mechanical properties compared to those formed from sisal fabric. The ageing of these fibres also changes the mechanical properties of the bio-composites compared to those having newly chopped sisal fibres.…”
Section: Introductionmentioning
confidence: 99%